2014
DOI: 10.1111/jar.12128
|View full text |Cite
|
Sign up to set email alerts
|

‘We Just Call Them People’: Positive Regard as a Dimension of Culture in Group Homes for People with Severe Intellectual Disability

Abstract: This positive cultural norm was established, operationalized and embedded through structures, such as a formal policy about language, and processes such as peer monitoring and practice leadership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…This perspective led to support staff acting as advocates of people with intellectual disabilities and to the provision of individualized support to assist people in achieving their own goals (Bigby et al, 2015;Kilroy et al, 2015). However, for some staff, these new roles conflicted with organizational procedures and priorities that limited the support provided to individuals once people had moved to community settings.…”
Section: Discussionmentioning
confidence: 98%
“…This perspective led to support staff acting as advocates of people with intellectual disabilities and to the provision of individualized support to assist people in achieving their own goals (Bigby et al, 2015;Kilroy et al, 2015). However, for some staff, these new roles conflicted with organizational procedures and priorities that limited the support provided to individuals once people had moved to community settings.…”
Section: Discussionmentioning
confidence: 98%
“…A larger ethnographic study of group homes with relatively poor outcomes identified five dimensions of culture; alignment of power holder values, regard for service users, perceived purpose, working practices, and orientation to change and ideas, as potentially applicable to all group home, and described the negative polar end of each dimension (Bigby et al 2012). A second study described the culture in 'better group homes' that rated well but not optimally on quality-of-life domains (Bigby, Knox, Beadle-Brown & Bould, 2014;Bigby et al 2015;Bigby & Beadle-Brown in press). Culture in better homes was characterized as coherent, enabling, motivating and respectful.…”
Section: Key Findings and Strength Of Evidence About Managerial Practicementioning
confidence: 99%
“…While research has uncovered the efforts of family members to influence service responses, and the difficulties they experience (Knox 2000;Bigby et al 2015), there is no specific evidence to support propositions about the positive influence of family involvement in supported accommodation services. There is, however, some evidence that family involvement and more well-resourced families gain better access to individualized funding packages (NeelyBarnes et al 2008) and lead to better post-school outcomes (Test et al 2009).…”
Section: Key Findings and Strength Of Evidence About Resources And Sementioning
confidence: 99%
“…Research shows that a staff's positive attitudes towards the capabilities of adults with PIMD facilitate their participation, whereas negative attitudes hinder participation (Bigby, Knox, Beadle-Brown, & Clement, 2015;Bigby, Knox, Beadle-Brown, Clement, & Mansell, 2012;Jones, Ouellette-Kuntz, Vilela, & Brown, 2008 To summarise, participation is a moving target. A large portion of the research on the participation of people with intellectual disabilities has focused on other people's abilities, attitudes and willingness to facilitate participation.…”
mentioning
confidence: 99%